2018
DOI: 10.1002/jcb.27891
|View full text |Cite
|
Sign up to set email alerts
|

A four‐gene signature predicts the efficacy of paclitaxel‐based neoadjuvant therapy in human epidermal growth factor receptor 2–negative breast cancer

Abstract: Neoadjuvant chemotherapy (NAC) is the major preoperative treatment of breast cancer (BC) with negative human epidermal growth factor receptor 2 (HER2), and the efficacy of NAC and the optimization of regimen are under intensive research. The current study aimed to define the predictive biomarkers for paclitaxel (PTX) response in NAC of HER2‐negative BC. Data from GSE25065, GSE26065, GSE41998, as well as drug sensitivity data of breast and ovarian cancer cell line from NCI60, were used. Through logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 45 publications
0
25
0
1
Order By: Relevance
“…Rixen and coworkers recently showed that MARC2 KO mice had decreased levels of total cholesterol and increased glucose levels, suggesting that MARC2 affects energy pathways [36]. However, Li et al showed that reduced MARC2 expression was associated with an increased sensitivity to paclitaxel-based neoadjuvant therapy in human EGFR-2-negative breast cancer patients [37] but, to the best of our knowledge, there have been no previous reports on a role of MARC2 in RCC.…”
Section: Discussionmentioning
confidence: 96%
“…Rixen and coworkers recently showed that MARC2 KO mice had decreased levels of total cholesterol and increased glucose levels, suggesting that MARC2 affects energy pathways [36]. However, Li et al showed that reduced MARC2 expression was associated with an increased sensitivity to paclitaxel-based neoadjuvant therapy in human EGFR-2-negative breast cancer patients [37] but, to the best of our knowledge, there have been no previous reports on a role of MARC2 in RCC.…”
Section: Discussionmentioning
confidence: 96%
“…17 Importantly, Li et al found that CDK8 was associated with sensitivity of PTX in NCI60 cells. 18 But the interaction among circ_0006528, miR-1299 and CDK8 in breast cancer remains unknown. This study aimed to explore the function of circ_0006528 in PTX resistance of breast cancer, and clarify the potential mechanism of circ_0006528 in PTXresistant breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…To be noted, NF-κB activation was proven to be involved in the tumor associated macrophages-mediated tumor growth in human pancreatic ductal adenocarcinoma [29]. PIMREG is known to positively regulate STAT3 activity to promote cell differentiation and shown to be associated with poor survival in the BC and pancreatic cancer [29][30][31][32]. It has been proven that both anti-and proinflammatory cytokines signal through associated receptor/JAK complexes and result in the phosphorylation of STAT3 [33].…”
Section: Discussionmentioning
confidence: 99%